Habitats around the world / [videorecording (DVD)]. (Start smart. Science I need to know.)
Why are habitats important? Questions are answered by introducing the animals and plants that live in different habitats around the world. Explore the polar regions, tundra, desert, grasslands, forests, and water habitats of the world! Incredible footage of animals in their natural environment is used to teach about the many fascinating habitats found on Earth. Even learn how to build an animal-friendly habitat in your own backyard!